Boundary values of solutions to linear second order parabolic equations - Skrypnik, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The local properties of the solutions of parabolic equations are investigated in domains whose boundaries are defined by the difference of two convex functions. Conditions for the existence of nontangential boundary and $L_2$ limits are established.